The implication of local animation TV series on Malaysian preschooler's personality / Nurul Atikah Adnan ...[et al.] - Adnan, Nurul Atikah; Primsuwan, Phaveena; Shawalludin, Syahrini (2019)
For many years, pre-schoolers are said to be interested in cartoons and therefore sometimes, their personality and thoughts are also based on their favourite cartoon character. Generally, children begin to watch cartoons as early as six months old, and by the age of two or three years old, they become the most enthusiastic audience. According to Aslin and Smith (1988), a baby's vision capability gets better when it grows. Children who spend their time watching cartoons tend to imitate the characters in the cartoons that they are watching. This may cause them to experience some negative and positive effects on the behaviour or personality development. According to Albert Bandura (1989), impersonation can be a tool for learning and it is a behavioural process through one's observation of individuals. Pre-schoolers see the characters as a model that will have an impact on their personality.